2022
DOI: 10.1109/tnsre.2022.3196828
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Transcranial Acoustoelectric Brain Imaging of Different Steady-State Visual Stimulation Paradigms

Abstract: Based on the acoustoelectric (AE) effect, transcranial acoustoelectric brain imaging (tABI) is of potential for brain functional imaging with high temporal and spatial resolution. With nonlinear and non-steady-state, brain electrical signal is microvolt level which makes the development of tABI more difficult. This study demonstrates for the first time in vivo tABI of different steady-state visual stimulation paradigms. Method: To obtain different brain activation maps, we designed three steady-state visual st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Besides, we have demonstrated that the pulse repetition frequency (PRF) of FUS is capable of encoding electroencephalography (EEG) signal and decoding AE signal and proved its feasibility through in vivo rat brain AEBI experiments [26][27][28][29][30][31]. Furtherly, based on PRF, living rat steady-state visual evoked potentials activation was mapped and the AE signal processing network of the rat brain was revealed [32][33][34][35]. The above studies made important contributions to optimize AEBI imaging method for further clinical application.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Besides, we have demonstrated that the pulse repetition frequency (PRF) of FUS is capable of encoding electroencephalography (EEG) signal and decoding AE signal and proved its feasibility through in vivo rat brain AEBI experiments [26][27][28][29][30][31]. Furtherly, based on PRF, living rat steady-state visual evoked potentials activation was mapped and the AE signal processing network of the rat brain was revealed [32][33][34][35]. The above studies made important contributions to optimize AEBI imaging method for further clinical application.…”
Section: Introductionmentioning
confidence: 85%
“…To evaluate AEBI image performance, the spatiotemporal resolution and imaging signal-to-noise ratio (SNR) were quantified. Spatial lateral (axial) resolution was defined as the width at 3 dB attenuation of AE signal peak which was measured along the x or y direction [24,28,34,45]. The SNR was calculated in decibels according to (7).…”
Section: E Evaluation Indicatorsmentioning
confidence: 99%